FORMATION OF HUMAN CAPITAL IN THE SOCIAL SPHERE IN THE CONDITIONS OF INNOVATIVE ECONOMY - Eskaliyeva, A.Zh.; Adietova, E.M.; Gabdulin, N.I. (Academic Journal of Physical and Chemical Sciences, 2018)
If initially human capital was defined through the prism of the immediate ability of a person (worker) to work, then over time the concept of human capital acquired new shades. Analytical socio-economic definition of human capital, i.e. The following definition can be considered as such which includes the possibility of management: human capital is an intensive factor of production, recently used as one of the indices of socio-economic development. Accounting for human capital in the structure of the national economy characterizes the degree of rationality of the attitude of the state, society and man to human existence, to its inclusion in the social institutions of a particular society. It is precisely because of the rational attitude towards man that human capital becomes not only the subject of theoretical study, but also the object of control.